2017
DOI: 10.1080/02699052.2016.1226385
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic baroreflexes and heart rate variability during acute stage of sport concussion recovery

Abstract: This study provides preliminary evidence that autonomic function is dysregulated following mTBI within the initial 72 hours of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 57 publications
1
82
0
1
Order By: Relevance
“…The HHb within‐subject results displayed a loss of statistically higher HHb SD after concussion, whereas D1–D3 and D4–D6 HbO 2 SD during hypercapnia was lower than resting values and statistically was different when compared to healthy controls. These haemoglobin SD results reinforce previous healthy variance research (that has utilized various measurement tools, under various physiological impairments), to show that variance in a given system is lost when one part of the system (or subsystem) no longer functions within a healthy range (Pincus, ; Coveney, ; Costa et al ., ; Papaioannou et al ., ; Cerutti et al ., ; La Fountaine et al ., ; Thayer et al ., ; Bishop & Neary, ; Bishop et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The HHb within‐subject results displayed a loss of statistically higher HHb SD after concussion, whereas D1–D3 and D4–D6 HbO 2 SD during hypercapnia was lower than resting values and statistically was different when compared to healthy controls. These haemoglobin SD results reinforce previous healthy variance research (that has utilized various measurement tools, under various physiological impairments), to show that variance in a given system is lost when one part of the system (or subsystem) no longer functions within a healthy range (Pincus, ; Coveney, ; Costa et al ., ; Papaioannou et al ., ; Cerutti et al ., ; La Fountaine et al ., ; Thayer et al ., ; Bishop & Neary, ; Bishop et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…To solve this concussion biomarker issue, some brain injury researchers have examined the frontal lobe's contribution to medullary function, which includes understanding how a loss of brain function exerts its effect on healthy variance of other physiological systems (Lang et al, 2003;Zweifel et al, 2008Zweifel et al, , 2010Ryan et al, 2011;Thayer et al, 2012;Len et al, 2013;Kontos et al, 2014;Blake et al, 2015;Urban et al, 2015;Bishop et al, 2017). This is because the frontal lobe can alter both the medulla's capacity to monitor the unconscious processes (such as cardiorespiratory status), and conscious processes such as reaction time and word recall (Goodale & Milner, 1992;Lovallo, 2005;Sakagami et al, 2006;Taylor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Bishop et al . () investigating HRV and blood pressure metrics during rest and cyclical squat‐stands (0·05 Hz: 10‐s squat hold/10‐s stand – the whole cycle lasting 20 s that corresponds to the frequency of 0·05 Hz, that is on the border of LF and VLF), it was found that there were no changes between groups or within‐subject regarding the LF during the haemodynamic and autonomic challenge protocol. Further, this demonstrates that the administration of such a test is safe for concussion patients as data showed that the protocol was well‐tolerable.…”
Section: Hrv Overview: Measurementmentioning
confidence: 99%
“…Research has demonstrated that blood flow–pressure regulation can alter cerebrovascular reactivity, autoregulation and neurovascular coupling (Jünger et al ., ; Len et al ., ; Bailey et al ., ; Bishop et al ., ; Wright et al ., ). These alterations may influence or contribute to HRV changes and thus will be briefly discussed here.…”
Section: Hrv Overview: Measurementmentioning
confidence: 99%
See 1 more Smart Citation